«Insile»: Contemporary Forms and Meanings of Exile - Tudela-Fournet, Miguel (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Through the study of the institution of exile, the different meanings and perceptions over time different traditions of political thought have given it, this work proposes to recover the meaning of exile, as a conceptual category, as «insile», to explain a number of social and political processes, with both individual and collective implications, of our contemporaneity.
Keywords: exile; insile; ancient greek and latin thought; postmodernity